Effect of Rehabilitation with a New Ocular Prosthesis on Electromyography of the Occipitofrontalis, Temporal, Masseter, and Sternocleidomastoid - De Caxias, Fernanda Pereira [UNESP]; Sa Teles, Karen Letícia [UNESP]; Santos, Daniela Micheline dos [UNESP]; De Moraes Melo Neto, Clóvis Lamartine [UNESP]; Da Silva, Emily Vivianne Freitas [UNESP]; Goiato, Marcelo Coelho [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP]; Januzzi, Marcella Santos; Turcio, Karina Helga [UNESP] (Thieme, 2021)
Objectives The aim of this study was to verify during facial expressions (happy, sad, fearful, angry, surprised, and disgusted) if: (1) there would be difference in the electromyography (EMG) of the occipitofrontalis, temporal, masseter, and sternocleidomastoid muscles on the normal side (NS) compared with the affected side (AS) (without the use of an ocular prosthesis) in individuals with unilateral absence of the eyeball, and (2) the rehabilitation with a new ocular prosthesis would affect the EMG of the muscles studied on the AS in these individuals. Materials and Methods Thirteen individuals, without temporomandibular disorder, with good health, with unilateral absence of the eyeball (the eye must have been removed by evisceration or enucleation), and users or nonusers of an ocular prosthesis were included. EMG of the occipitofrontalis, temporal, masseter, and sternocleidomastoid muscles was performed during rest and facial expressions (happy, sad, fearful, angry, surprised, and disgusted) before (T0) and 90 days after (T1) rehabilitation with a new ocular prosthesis. The analyses were performed in T0 on NS and AS (without the use of an ocular prosthesis), and in T1 on AS with the new ocular prosthesis. Statistical Analysis All data were submitted to the Student's t -test with p < 0.05. Results There was no statistically significant difference comparing the AS with the NS in T0 for all muscles studied, during all facial expressions evaluated (p > 0.05). There was no statistically significant difference comparing the AS in T0 with itself in T1 for all muscles studied, during all facial expressions evaluated (p > 0.05). Conclusion Eye loss did not affect the EMG of studied muscles when comparing NS with AS (without the use of an ocular prosthesis). The rehabilitation with ocular prosthesis was not capable of changing the EMG on AS.
Keywords: electromyography; eye; facial muscles; masseter muscle; ocular prosthesis; temporal muscle